Phosphorylation of pRb: mechanism for RB pathway inactivation in MYCN‐amplified retinoblastoma - Ewens, Kathryn G. (Cancer Med, 2017)
A small, but unique subgroup of retinoblastoma has been identified with no detectable mutation in the retinoblastoma gene (RB1) and with high levels of MYCN gene amplification. This manuscript investigated alternate pathways of inactivating pRb, the encoded protein in these tumors. We analyzed the mutation status of the RB1 gene and MYCN copy number in a series of 245 unilateral retinoblastomas, and the phosphorylation status of pRb in a subset of five tumors using immunohistochemistry. There were 203 tumors with two mutations in RB1 (RB1 (−/−), 83%), 29 with one (RB1 (+/−), 12%) and 13 with no detectable mutations (RB1 (+/+), 5%). Eighteen tumors carried MYCN amplification between 29 and 110 copies: 12 had two (RB1 (−/−)) or one RB1 (RB1 (+/−)) mutations, while six had no mutations (RB1 (+/+)). Immunohistochemical staining of tumor sections with antibodies against pRb and phosphorylated Rb (ppRb) displayed high levels of pRb and ppRb in both RB1 (+/+) and RB1 (+/−) tumors with MYCN amplification compared to no expression of these proteins in a classic RB1 (−/−), MYCN‐low tumor. These results establish that high MYCN amplification can be present in retinoblastoma with or without coding sequence mutations in the RB1 gene. The functional state of pRb is inferred to be inactive due to phosphorylation of pRb in the MYCN‐amplified retinoblastoma without coding sequence mutations. This makes inactivation of RB1 by gene mutation or its protein product, pRb, by protein phosphorylation, a necessary condition for initiating retinoblastoma tumorigenesis, independent of MYCN amplification.